Phototherapy as the tool of emotional identification development of adolescents - Tyron, Olena; Dotsenko, Ludmyla; Kariaka, Inna (Journal of Education and Learning (EduLearn), 2024)
The results of the empirical stage statistically proved that phototherapy is one of the effective tools of psycho-pedagogical assistance to adolescents who experience difficulties associated with emotional identification. We diagnosed the level of formation of this phenomenon within the sample of 240 respondents who are university and school students aged 17 to 20 years female and male. A number of psycho-diagnostic methods were used in the study: the method 'Toron to alexithymia scale (TAS-26)” and the questionnaire “self-attitude.” Summarizing the results, we state that most of the studied sample is in a state of emotional well-being but emotional discomfort occurs among some respondents with certain levels of propensity for alexithymia (22.5%). The research proves the positive impact of phototherapy on adolescents' emotional identification development through photographing and creating visual pictures or direct perception and interpretation of images.